Introduction to NJWLS 2022-3 - Buch, Anders (Nordic Journal of Working Life Studies, 2022)
The third issue of volume 12 of Nordic Journal of Working Life Studies brings four new research articles and a book review. The first article of this issue is authored by Helena Håkansson: Contradictions of Ordered Trust: Trust-based Work and Conflicting Logics in Municipal Care. In this article, Håkansson explores the implementation of a trust-based development project in the social care service in a municipal district in Sweden. The research took place in 2017–2019 and comprised semi-structured interviews and observations among managers and staff involved in the project. Using an institutional logics framework to interpret and discuss the findings, Håkansson illuminates how a managerial logic and a logic of care manifests themselves, and how the logics relate to power structures in the organization. She shows how the managerial logic tends to relativize trust into a question of financial accountability, and highlights the inherent paradox of ordering trust as a one- way communication by the upper management.